Fabrication of fish scaling machine / Adam Habri - Habri, Adam (2023)
A Fish scaling machine is a newly developed product according to the food processing industry that is in demand in the market. Due to the difficulty in removing fish scale manually, this project objective is to fabricate a fish scaling machine to help the process of removing the scale easier and less time consuming. This project intends to design, analyze, and fabricate a fish scaling machine that will help to reduce the process time and reduce the hassle to remove fish scales than removing he fish scales using the normal method. The fish scaling machine can reduce the time of the process because it is powered by an electric motor. In conclusion, the machine will surely benefit a small industry that uses fish.